2017
DOI: 10.1590/0004-282x20170070
|View full text |Cite
|
Sign up to set email alerts
|

Late onset multiple sclerosis: concerns in aging patients

Abstract: Late onset multiple sclerosis (LOMS) is when the first symptom starts after 50 years of age, representing 4.5% of multiple sclerosis (MS) patients. This study describes the clinical characteristics of patients with LOMS followed at a specialized MS center in São Paulo. Data was obtained from medical records of 742 patients with MS. The LOMS frequency was 4.18%, median age at onset was 54 years and the predominant disease course was primary progressive (64.3%). The patients reached the disability landmarks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
(84 reference statements)
3
15
0
Order By: Relevance
“…In our study, a high percentage of patients had OCBs in CSF, and this was observed across all age groups, consistent with other studies [9,10,24,30], which indicates that OCB is an effective diagnostic tool in patients of all ages. Patients with abnormal VEP also predominated in our study, in line with the work of Kis et al (AOMS: 70%; LOMS: 86%) [9] and Noseworthy et al (AOMS: 67%; LOMS: 62%) [43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, a high percentage of patients had OCBs in CSF, and this was observed across all age groups, consistent with other studies [9,10,24,30], which indicates that OCB is an effective diagnostic tool in patients of all ages. Patients with abnormal VEP also predominated in our study, in line with the work of Kis et al (AOMS: 70%; LOMS: 86%) [9] and Noseworthy et al (AOMS: 67%; LOMS: 62%) [43].…”
Section: Discussionsupporting
confidence: 92%
“…The presence of motor symptoms was found to be higher as age increased. Our findings are similar to those in studies comparing patients with AOMS and LOMS, where motor deficit was found to be the most common neurological manifestation among late-onset patients, encompassing more than half of the studied group (54.8-80%) [6,9,10,12,13,24,25]. Overrepresentation of motor deficit in older patients may be connected to the overrepresentation of the primary progressive form of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…Some recent reports indicate an increasing numbers of patients with MS late onset, after 50 years of age [46,47]. We observed similar data in the 40-year follow-up of the prevalence in Ferrara, which demonstrates an increasing number of subjects with the late onset of the disease and a relatively increasing age at onset patients.…”
Section: Discussionsupporting
confidence: 88%
“…In Ferrara, the mean age had increased by about 4 years, 30.8 ± 9.6 years in 1978 and 34 ± 10.8 years in 2017. The late onset, associated mainly with a progressive course, seems to be predictor of reaching EDSS 3.0 and 6.0 in a short time [47].…”
Section: Discussionmentioning
confidence: 88%
“…Following Krupp et al [18], participants were identified as having early onset MS (EOMS), if at disease onset their age was 18 years or under. Following Lotti et al [19], participants were identified as late onset of MS (LOMS), if at disease onset they were 50 years or older. Participants were identified as having adult onset MS (AOMS), if at disease onset they were between 18 and 49.9 years old.…”
Section: Samplementioning
confidence: 99%